2020
DOI: 10.1002/jmrs.451
|View full text |Cite
|
Sign up to set email alerts
|

The proportion of computed tomography kidneys, ureters and bladder (CTKUB) scans that comply with scan extent protocol in an emergency department: a clinical audit and dose ramification study

Abstract: Introduction To assess computed tomography kidneys, ureters and bladder (CTKUB) scan extent protocol compliance and associated doses in the Emergency Department (ED) of an Australian tertiary hospital. Methods A retrospective clinical audit of 150 consecutive ED CTKUB cases was completed. For each patient, scan extent compliance at the superior (kidneys) and inferior (pubic symphysis) borders, in reference to the protocol was recorded. Compliance and non‐compliance (over‐/under‐scanning) was identified, descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 26 publications
(74 reference statements)
0
1
0
Order By: Relevance
“…The results of our study align with the high rate of CT over-scanning demonstrated in previous studies of current literature [5,6,[11][12][13]. The increase in scanning range results in unnecessary radiation dose to the patients.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The results of our study align with the high rate of CT over-scanning demonstrated in previous studies of current literature [5,6,[11][12][13]. The increase in scanning range results in unnecessary radiation dose to the patients.…”
Section: Discussionsupporting
confidence: 90%
“…For abdomen/pelvis CT scans, just above diaphragm is used as the start point of the scan. The inferior aspect of the pubic symphysis is used as the endpoint of the scan to measure the over and under-scanning length [4,[6][7][8]. and confirmed to be within acceptable range.…”
Section: Introductionmentioning
confidence: 99%
“…However, in adults, the ACR and AUA both recommend CT as the first-line investigation for symptoms of obstructive nephrolithiasis. The sensitivity and specificity of CT scans are 95% and 98% respectively, which is proved by a recent review to be of higher values than all other imaging modalities, including MRI, ultrasound, or plain radiographs [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Identification of the uppermost renal point on axial imaging was performed to calculate additional scans, involving a comparison between slices above this point and the total axial slices. In the study by Kasi et al, IMPAX measurements were integrated as part of the assessment [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite proven accuracy, adoption of this technology has been slow [18 ▪ ,19,20], with an increase from 2% in 2011 to only 7.6% in 2015 [21]. Unnecessary radiation exposure is a result of incorrectly protocolled imaging with multiple phases or over-scanning above or below the area of interest [18 ▪ ,22]. Further, there is wide variation both within and between hospitals [20].…”
Section: Reducing Radiation Exposure: ’As Low As Reasonably Achievable’mentioning
confidence: 99%